Impact of differing frequencies of PETTLEP imagery on netball shooting performance - Wakefield, C. J.; Smith, D. (Journal of Imagery Research in Sport and Physical Activity, 2009)
This study examined the effects of differing frequencies of PETTLEP imagery on netball shooting performance. Thirty-two female participants were divided into four groups: PETTLEP imagery once per week (1x/wk), PETTLEP imagery twice per week (2x/wk), PETTLEP imagery three times per week (3x/wk) and a control. During the pre-test and post-test participants were required to complete a total of twenty shots from five different points within the shooting zone. They were awarded points (out of five) for each shot, giving a possible total of 100 points. The numbers of shots scored was also recorded. Following the pre-test, the imagery participants imaged the twenty shots the required number of times per week. The control group completed some netball specific stretching. Transfer tests were also completed to assess the transferability of the intervention to related tasks. Group x test ANOVAs for performance score and shots scored revealed a significant interaction effect (p<.01). Tukey tests revealed that the 3x/wk imagery group improved performance on both measures, whereas the 2x/wk, 1x/wk and control group did not. These results support the notion that PETTLEP imagery may be more effective if completed at least three times per week.